KEPERCAYAAN MEDIA DAN PEMENUHAN KEBUTUHAN INFORMASI SUPORTER SEPAKBOLA MELALUI MEDIA SOSIAL DI ERA DIGITAL - Nurdiantara, Robby Rachman; Rabathy, Qisthy; Wahyono, Herry Setianto (Linimasa : Jurnal Ilmu Komunikasi, 2024)
Online media and social media as new media in the digital era, are connected and support each other, providing easier and wider access and information for their audiences. Currently, the popularity of social media is increasing, used by audiences to communicate, interact, and obtain and share information. Social media is used by online media owners to reach a wider audience, Simamaung.com is one of the online media which used Twitter social media to provide news and information about Persib Bandung Football to supporters, namely Bobotoh. But, currently there are so many sources of information originating from online media, so media trust has become important for supporters as an audience to choose the right source of information to follow and trust. This research aims to carry out descriptive and correlational analysis and correlational analysis about the correlational between media trust and fulfilling Bobotoh Persib's information needs for Simamaung.com In twitter. Used survey research methods with purposive sampling techniques to Bobotoh Persib who follow the official Twitter account Simamaung.com, by conducting descriptive and correlational data analysis using the SPSS program. The descriptive analysis results showed that media trust and fulfilling the information needs from Bobotoh Persib on the Twitter of Simamaung.com is very high. And then the correlational analysis results showed that there is a significant positive correlational between media trust and fulfilling the information needs of Bobotoh Persib on the Twitter of Simamaung.com. This study also showed, if the media trust is high, so then fulfilling the information needs of Bobotoh Persib on Twitter of Simamaung.com will also be high too. Keywords: Fulfilling the Information Needs, Football Fans, Media Trust, New Media, Twitter.